“SAD”- A medical undergraduate centered cross-sectional study from a teaching tertiary medical institution in North east India - Ms. Yashika Parashar,Dr. Sharat Agarwal*,Dr. Manika Agarwal (Innovative Journal of Medical and Health Sciences, 2019)
Background- Stress, Anxiety and Depression disorders are common problems among the youth today especially among the students of professional courses.[1] Our study aims to find the levels of stress, anxiety and depression among medical students, their probable causes and suggest certain measures to control them. Undergraduate medical education in India comprises strenuous study and training for 5.5 years. It has been reported that medical students consequently suffer from depression, anxiety, and stress. It has been reported that healthy students develop depression and stress after commencing their medical education. [2] The competition for getting postgraduate training and seeking job opportunities could be an additional trigger for psychological illness. It has also been reported that physicians tend to have a higher suicide rate than the general population. [3] Aim- Our study was aimed at finding stress, anxiety and depression levels amongst MBBS students of North East India. Methods- A total of 120 questionnaires were distributed among the MBBS Students of different academic years out of which 108 responses were received out of which 100 were completed questionnaires and were included for the study. The remaining 20 questionnaires were either not returned or were incomplete, hence were excluded from the study. Results-Among the mental health problems that were assessed, anxiety disorders are the most common. Following anxiety, students are affected the most by depression while stress disorders are the least common. Most of the students felt that they were under academic stress and it can possibly be one of the major reasons for anxiety and stress among them. Interestingly, it was found that the participants felt that gender doesn’t play an important role in causing stress but the stress, anxiety and depression levels were found to be higher or equal among the females than the males.The students feel that drug intake and peer pressure was not the cause for adding on to their mental stress. However, the increased usage of internet and time spent on social media can be correlated to the increasing problems among the students as was found in our study. Conclusion-There is an urgent need to tackle the problem of increasing mental health problems among medical students as emphasised through this study conducted in a tertiary care level medical institute in the North Eastern part of India. Key words- MBBS students, Northeast India, Stress, Anxiety, Depression